Design and modelling of novel evacuated receiver tube of concentration solar power system by using heliostat stadium arrangement - Kadhim Khlief, A. (EDP Sciences, 2017)
A novel concentration solar evacuated receiver tube collector is proposed in this study. Details of design and simulation of the heliostat field are presented. The proposed system uses a heliostat stadium arrangement to focus sunlight towards a receiver (evacuated receiver tube). Heliostat field which looks like stadium arrangement is proposed an alternative system of the tower in the power tower plants to cancel the shading / blocking losses. In this study, simulation results showed that the energy input increases with increased solar irradiation; the increase ranges from 288 to 470W/m.The maximum amount of energy inputs that can be obtained in the receiver for the collector is around 470W/m for the maximum solar density of 688W.m2. In the solar is 402 W/m2, and the useful energy of collectors is about 288 W/m and the thermal efficiency of the receiver was around 23. © The authors, published by EDP Sciences, 2017.